17/13+9/4-l1+4/13l-2/4
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: =-5/11-6/11+1=-11/11+1=0
b: =-13/17-13/21-4/17=-1-13/21=-34/21
b: \(=-\dfrac{5}{12}\cdot\dfrac{9}{20}\cdot\dfrac{7}{17}=\dfrac{-21}{272}\)
d: \(=\dfrac{13}{17}\left(-\dfrac{4}{5}-\dfrac{3}{4}\right)=\dfrac{13}{17}\cdot\dfrac{-31}{20}=\dfrac{-403}{340}\)
Lời giải:
$\frac{4}{9}\times \frac{-13}{-17}+\frac{-2}{17}\times \frac{4}{9}+\frac{2}{9}\times \frac{4}{17}$
$=\frac{4}{9}\times (\frac{13}{17}+\frac{-2}{17})+\frac{2}{9}\times \frac{4}{17}$
$=\frac{4}{9}\times \frac{11}{17}+\frac{4}{9}\times \frac{2}{17}$
$=\frac{4}{9}\times (\frac{11}{17}+\frac{2}{17})$
$=\frac{4}{9}\times \frac{13}{17}=\frac{52}{153}$
a: \(=-\dfrac{5}{12}\cdot\dfrac{9}{20}\cdot\dfrac{7}{17}=-\dfrac{21}{272}\)
b: \(=\dfrac{13}{17}\left(-\dfrac{4}{5}-\dfrac{3}{4}\right)=\dfrac{-13}{17}\cdot\dfrac{31}{20}=-\dfrac{403}{340}\)
c: \(=\dfrac{-5}{7}\left(\dfrac{2}{11}+\dfrac{9}{11}\right)+\dfrac{5}{7}=-\dfrac{5}{7}+\dfrac{5}{7}=0\)
d: \(=\dfrac{12}{5}-\dfrac{3}{10}=\dfrac{21}{10}\)
a: =35/17-18/17-9/5+4/5
=1-1=0
b: =-7/19(3/17+8/11-1)
=7/19*18/187=126/3553
c: =26/15-11/15-17/3-6/13
=1-6/13-17/3
=7/13-17/3=-200/39
a: =-5/9-4/9+8/15+7/15-2/11=-2/11
b: =10/17+7/17-5/13-8/13+11/25
=11/25
c: =(9/12-2/12)*3/2=7/12*3/2=21/24=7/8
d: =(31/10-25/10)*3-2
=3/5*3-2
=9/5-2
=-1/5
Gọi A=4/5.9+4/9.13+4/13.17+...+4/41.45
4.A=4.4/5.9+4.4/9.13+...+4.4/41.45
A=4/5-4/9+4/9-4/13+...+4/41-4/45
A=4/5-4/45
A=32/45
Vậy 4/5.9+4/9.13+...+4/41.45=32/45
\(\dfrac{17}{4}+\dfrac{9}{4}-\left|1+\dfrac{4}{13}\right|-\dfrac{2}{4}\\ =\dfrac{17}{4}+\dfrac{9}{4}-\left|\dfrac{13}{13}+\dfrac{4}{13}\right|-\dfrac{2}{4}\\ =\dfrac{17}{4}+\dfrac{9}{4}-\dfrac{17}{13}-\dfrac{2}{4}\\ =\left(\dfrac{17}{4}+\dfrac{9}{4}-\dfrac{2}{4}\right)-\dfrac{17}{13}\\ =\dfrac{24}{4}-\dfrac{17}{13}\\ =6-\dfrac{17}{13}\\ =\dfrac{61}{13}\)
Cíu túi :(((((